Manfaat Dan Keunggulan Mekanisme Penggunaan Asuransi Simas Sehat Gold Terhadap Nasabah - Saskhia Azzahra; Madian Muhammad Muchlis (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
In today's era and the changing and needs regarding a good health system, health insurance has a very important role in supporting universal access to health services and protecting individuals and families from unexpected financial risks. Thus, this research aims as an educational material for the wider community, especially in Indonesia, which is actually in dire need of health insurance but still in doubt about its benefits and financial value. In this research, the author uses a qualitative research approach in the form of a library study (Library Research). The result of this research is that Simas Sehat Gold Insurance for customers has many benefits including: (1) Customers can already enjoy a cashless system. (2) Customers under the age of 50 do not need a medical examination. (3) Simas Sehat Gold Insurance can be paid in installments per month through a Visa or Mastercard credit card. (4) There is free personal accident insurance worth Rp 10 Million. (5) There are emergency medical evacuation guarantees around the world. And the advantages of Simas Sehat Gold insurance products include using a cashless system and products from PT. Sinar Mas Insurance has a wider range of hospital providers or partners so that customers are easier to find and receive by the hospital.